Evaluation of drug–drug interactions of a novel potent FLT3 inhibitor SKLB1028 in healthy subjects - Chen, Jingcheng; Wu, Jingxuan; Guo, Nini; Song, Yuqin; Li, Lijun; Wang, Bingyan; Li, Jiangshuo; Hou, Mengyu; Yin, Hang; Zhang, Meijuan; Kong, Yanhong; Wu, Xiaofang; et al. (Clinical and translational science, 2024)
SKLB1028 is a novel multi‐target protein kinase inhibitor under investigation for the treatment of FLT3‐ITD mutated acute myeloid leukemia. Based on the preclinical characterization of SKLB1028 metabolism, three drug–drug interaction clinical studies were performed to investigate the effects of itraconazole, rifampin (CYP3A4 inhibitor and inducer, respectively), and gemfibrozil (CYP2C8 inhibitor) on the metabolism of SKLB1028. Fourteen healthy Chinese male subjects were enrolled in each study. In Study 1, subjects were administered a single dose of SKLB1028 (100 mg on days 1 and 11) and multiple doses of itraconazole (200 mg twice daily on day 8 and 200 mg once daily from days 9 to 18). Itraconazole was given with a loading dose on Day 8 and the total administration of itraconazole was 11 days. In Study 2, subjects were administered a single dose of SKLB1028 (100 mg on days 1 and 12) and multiple doses of gemfibrozil (600 mg twice daily from days 8 to 19). In Study 3, subjects were administered a single dose of SKLB1028 (150 mg on days 1 and 15) and multiple doses of rifampin (600 mg once daily from day 8 to 22). Itraconazole increased the AUC and Cmax of SKLB1028 by approximately 28% and 41%, respectively. Compared to the single drug, co‐administration with gemfibrozil increased the AUC of SKLB1028 by ~26% and the Cmax by ~21%. Co‐administration with rifampin reduced the AUC of SKLB1028 by ~30%, while the Cmax did not change significantly. All treatments were well tolerated in all three studies.